The Basic Influence of Movement Skills through the Media of Snakes on Improving Gross Motorcycle - Resfa, Virda Lutvia; Lengkana , Anggi Setia; Mulyanto, Respaty (Indonesian Journal of Sport Management, 2024)
This research aims to test the influence of the Snakes and Ladders media with the Fundamental Movement Skills test on improving students' gross motor skills. Based on the nature of this research, to try this, this research uses an instrument, namely using Trs Fundamental movement skills with a movement guide, namely using gross motor skills movements, to see how much influence it has on the child's gross motor skills. The research design used is a pre-experimental group pretest–post-test design, which only processes data from the Pretest and post-test results. Data analysis in this study used SPSS version 21, which includes a normality test, descriptive test, and Wilcoxon test. The subjects in this research were 38 upper-class children at Sdn Permata Hijau Bandung for rational reasons. The research results show that the descriptive data produces a minimum pretest score of 19 and a post-test of, a maximum pretest score of 5, and a top post-test score of 70. The average or average pretest score is 45.39, and the average post-test score is 54.76; the standard deviation on the Pretest was 11.645, and the post-test was 15.853. Meanwhile, in the normality test, the Sig value is <0.05, which means the Sig value is rejected or abnormal. The researcher applied the Wilcoxon Test to look for concrete results in this research, and the result was that the results for the negative ratings of 33 respondents did not decrease, either from the average rating (average) or the number of ratings (total).